Redescription of Acanthochitona mahensis Winckworth, 1927 (Polyplacophora, Acanthochitonidae) from Indian Coasts - Thomas, Liju; Anseeuw, Bruno; Ranjeet Kutty; Parambil, Sooraj Kandathil (Zootaxa, 2023)
A redescription of the chiton species Acanthochitona mahensis collected from the type locality is provided and its holotype is studied. This species has been previously recorded from the coasts of India, Pakistan, Sri Lanka, Eritrea, and Jordan. It is compared with similar species (Acanthochitona biformis, A. jugotenuis, A. intermedia, A. leopoldi, A. penicillata and A. woodwardi). In India, the species has been reported from the mainland and Andaman Islands. New distributional records from the coast of India are also provided.